2004
DOI: 10.1016/s0035-9203(03)00005-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of two antivenoms for the treatment of Bothrops and Lachesis bites in the north eastern Amazon region of Brazil

Abstract: The efficacies of specific Bothrops atrox-Lachesis and standard Bothrops-Lachesis antivenoms were compared in the north eastern Amazon region of Brazil. The main aim was to investigate whether a specific antivenom raised against the venom of B. atrox, the most important Amazon snake species from a medical point of view, was necessary for the treatment of patients in this region. Seventy-four patients with local and systemic effects of envenoming by Bothrops or Lachesis snakes were randomly allocated to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
1
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 30 publications
14
110
1
10
Order By: Relevance
“…B atrox is notorious as the leading cause of severe snake bites wherever it occurs in South America 4 16. In contrast, B bilineatus , a distinctive bright green arboreal snake, is less well known as a snake of real medical importance 30.…”
Section: Discussionmentioning
confidence: 99%
“…B atrox is notorious as the leading cause of severe snake bites wherever it occurs in South America 4 16. In contrast, B bilineatus , a distinctive bright green arboreal snake, is less well known as a snake of real medical importance 30.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of PIII-SVMPs in B. atrox venom is strongly correlated with the symptoms of human envenomings by this species [21]. Venom metalloproteinases, particularly PIII-SVMPs, are responsible for the local and systemic hemorrhage and are also involved in the local lesions due to their pro-inflammatory action or the ischemia at the site of the bite which arises from the reduction of blood supply following the damage of microvasculature [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of antivenom in treating local toxicity due to viper venoms was equivocal in several clinical trials evaluating systemic effects (7)(8)(9)(10). A retrospective study found that antivenom administration was associated with less severe edema after Vipera Berus envenomation (11).…”
Section: Introductionmentioning
confidence: 99%